How Filipinos make a difference: Exploring the role of digital transformation and traditional social innovation in generating digital social innovation among selected social enterprises - Fernandez, Danzel Rafter Y. (Animo Repository, 2022)
Digital transformation (DT) is catalyzing the evolution of the global economy, and this evolution has widely affected the functioning of social enterprises (SEs), and has then transformed traditional social innovation (SI) to the digital landscape, generating digital social innovation (DSI). Through qualitative research methods of interviews and FGDs, as supported by descriptive statistics from surveys, it was found that both DT and SI generate DSI across selected SEs: CP Health Innovations, Juan Balikbayan, and Handcrafted by Harls. Through semi-structured interviews, the main themes of significance of digitalization, limited transparency, data-driven decisions, use of communication, stakeholder integration, ease of business operations, and social purpose were found to be prevalent among social entrepreneurs and their social enterprises. Across the observed SEs, it was evident that DT was demonstrated to a fairly good extent, SI to a great extent, and DSI to a likewise great extent. Conclusively, DT, though applied to different degrees across social enterprises, allows these enterprises to accommodate for data-driven decisions, business visibility, and process efficiency improvement; while SI legitimizes the social purpose of enterprises and empowers collaborations. DSI, with DT and SI, is generated by SEs through stakeholder integration, social support infrastructure, and improving their quality of solutions